Patent Right: Comparative Study in Perspective of Shariah and Law - Ali, Hafiz Nasir (Journal of Islamic and Religious Studies, 2021)
The world has taken the shape of globalization due to the rapid development in modern times. Thanks to the proliferation of inventions, modern methods of trade have become the norm, which has given rise to an endless series of modern jurisprudential issues concerning trade and affairs. Many types of personal rights have become prevalent in modern times that have no real sensory existence, but their transactions through buying and selling in the market are common, such as turbans of houses and shops, specific trademarks, use of commercial licenses, rights Authorship and publication, sale of atmosphere, etc. One of these rights is "patent right". What is the Islamic and legal concept about this? Is it permissible to buy or sell it? This article attempts to draw a comparison between the Islamic perspective on patent rights and its legal issues. The study concludes that buying and selling patent rights is permissible according to the laws and fatwās of most of the jurists. Moreover, according to Islamic teachings, it is forbidden to invent and use devices that cause problems and suffering to human life.